Energetic, economic, exergetic, and exergorisk (4E) analyses of a novel multi-generation energy system assisted with bagasse-biomass gasifier and multi-effect desalination unit. (15th March 2021) - Safder, Usman; Nguyen, Hai-Tra; Ifaei, Pouya; Yoo, ChangKyoo
Abstract: This study presents a novel multi-generation system (MGS) assisted by sugarcane bagasse to produce power, freshwater, and cooling. The proposed integrated MGS consisted of a bagasse-biomass based gasifier-Brayton cycle, a Rankine cycle, a Kalina cycle, an ejector refrigeration cycle, and a multi-effect desalination unit. Comprehensive energy, economic, exergy, exergorisk (4E) analyses of the proposed system were performed. The effects of operating parameters on thermodynamic performance and economic feasibility were investigated. An optimal configuration of the proposed system was determined via weighted multi-objective optimization approach considering exergorisk, exergy, and economic analyses. The results showed that bagasse-biomass flowrate was the dominant factor affecting variation in energy and exergy efficiencies, and total cost rate. An increase in bagasse-biomass flowrate from 1.5 kg/s to 10 kg/s led to decreases of 34.42% and 50.75% in overall energy and exergy efficiencies. The most substantial increase (43.07%) in exergy efficiency occurred at a high compression ratio. The optimization results showed that the total accidental risk impact was improved by 92.59% and energetic and exergetic efficiency was increased to 92.10% and 77.49%, respectively. The proposed optimum system can provide power, cooling, and freshwater at loads of 28.72 MW, 13.64 kg/s, and 3.43 MW, respectively. Graphical abstract: Image 1 Highlights: Bagasse gasification based novel sustainable multi-generation system is proposed. Investigating sensitivity of system performance and costs to the key parameters. The system is optimized decreasing total cost rate and exergorsik analysis. Optimized system has high energetic and exergetic efficiency (92.1% and 77.49%). Bagasse biomass contribution leads to higher power generation.